Strength and durability study on cement mortar with ceramic waste and micro-silica. (2018) - Nayana, A.M.; Rakesh, P.
Abstract: This study shows the properties of cement mortar made with crushed ceramic waste and micro-silica by partially replacing sand and cement respectively. The effect of these recycled materials was examined by conducting tests like compressive strength test and durability tests such as rate of water absorption, sorptivity test and sulfate attack test. In this study, mortar mixes are produced by replacing a fraction of cement by 5% and 10% with micro-silica and sand by 15%, 30% and 50% with ceramic waste. The mechanical and durability properties were evaluated for different mixes and compared it with reference mix. The compressive strength of recycled mortar increases with 15% ceramic and 10% micro-silica content by 20.78% when compared with control mix and then decreases with further addition of ceramic waste. The rate of water absorption has reduced by 1.17% for mix with 15% ceramic waste and 0% micro-silica when compared with reference mix and sorptivity has reduced by 11.96% for mix with 15% ceramic waste and 0% micro-silica when compared with reference mix. The expansion of the mortar remained lower for mix with 15% ceramic waste when compared with other mixes Microstructure was also analysed using Scanning Electron Microscope (SEM).